ANALISIS TITIK PULANG POKOK PADA USAHA JAMUR TIRAM DI DESA MPANAU KECAMATAN BIROMARU KABUPATEN SIGI - Anwar, Astan; Lamusa, Arifuddin; Effendy, Effendy (AGROTEKBIS, 2017)
The study aims to determine the amount of revenue earned and expenses incurred, know the size of the resulting production and sales value received in the Village Oyster Mushroom Business District of Mpanau Biromaru Sigi. The study was conducted in the village of Oyster Mushroom Business District of Mpanau Biromaru Sigi in October to December 2015. The respondents consisted of two persons namely business owners and labor one person of Business Oyster Mushrooms. The results indicate the that study: (1). The revenue the that oyster mushroom business are products IDR. 5,250,000/month with a production cost of IDR. 3,032,268/month, in order to obtain of revenue IDR. 2,217,732/month. (2). The break even point for the product achieved in the oyster mushroom production volume as much as 51 kg at a price of IDR. 35,000/kg, the sales value of IDR. 1,785,000/month. This could mean that if these efforts produce results of more than 51 kg or gain more acceptance, then the business will have an advantage, otherwise if the business is producing less than 51 kg or receiving less then this business will suffer losses. Key Words: Analysis of break event point, Oyster mushroom business in Mpanau Viilage.